2020
DOI: 10.1590/1517-869220202602188454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated-Sprint Training in Hypoxia on Physical Performance of Team Sports Players

Abstract: Introduction: The traditional hypoxic training program used by endurance athletes was included in the training of team and/or racquet sports players. Objective: The aim of this study is to analyse the effect of a new lower dose of repeated-sprint training in hypoxia (RSH) as compared with previous studies on short and long-term physical performance of team sports players. Methods: Tests were performed before and after four weeks of supervised specific training and after two weeks of detraining. Twenty-four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…395). Statistically significant progress of the experimental and control groups (15 -33 %) was found in three studies (Brocherie et al, 2015b;Hamlin et al;Camacho-Cardenosa et al). For more details, see Table III.…”
Section: Study Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…395). Statistically significant progress of the experimental and control groups (15 -33 %) was found in three studies (Brocherie et al, 2015b;Hamlin et al;Camacho-Cardenosa et al). For more details, see Table III.…”
Section: Study Resultsmentioning
confidence: 88%
“…In order to assess the impact of RSH training method on the produced maximum or average strength, the authors of two studies included in this systematic review used the Wingate test for 30s as a testing protocol (Faiss et al, 2013;Camacho-Cardenosa et al) where progress was found in both studies, but without statistical significance (p > 0.05). For more details, see Table IV.…”
Section: Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations